Three years of the specialized seminar-workshop on research in the teaching of history at the College of History of the UNAM - Ordóñez, Michelle (Universidad Nacional del Litoral, 2022)
In May 2018 I discovered that I had been removed from the list of teachers who teaches the subject Teaching of history in the history degree of the College of History of the Faculty of Philosophy and Letters of the UNAM. The coordinator pointed out that a staff rotation was necessary for us to update and innovate our practices. He offered me to teach a specialized seminar-workshop that received, mainly, fifth-semester students, however, since it was optional, there was a risk that the group would not open due to lack of interest in the proposed topic. Based on my experience as a teacher and member of the admission committees in the history field of the Master's Degree in Teaching for Higher Secondary Education, I decided that I had an opportunity to provide tools that would make it possible to problematize the teaching of history and propose relevant and pertinent research. This is how the seminar-workshop specialized in research in history teaching arose, of which I offer a systematization that analyzes students, contents and production of the course, in order to reflect on the need to include research as an essential knowledge for teachers of history.